Advancements in additive manufacturing for video laryngoscopes: a comprehensive scoping and technological review - Ana Cristina Beitia Kraemer Moraes; Chiara das Dores do Nascimento; Everton Granemann Souza; Mauricio Beitia Kraemer; Mauricio Moraes; Neftali Lenin Villarreal Carreno; Evandro Piva; Rafael Guerra Lund (Systematic Reviews, 2023)
Abstract The global healthcare crisis with the COVID-19 pandemic has placed a significant overwhelming demand for intubation procedures and the need for reliable and accessible video laryngoscopes. The purpose of this scoping and technological review is to provide a comprehensive overview of the current state of the art, covering the period from 2007 to 2022, pertaining to the manufacturing process, characteristics, and validation of video laryngoscopes produced using additive manufacturing techniques. Following the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR), an exhaustive search was conducted across nine prominent databases (PubMed, Web of Science, Scopus, Cochrane, Prospero, Scielo, Embase, Lilacs, Virtual Health Libraries-VHL) and four patent databases (EPO/ESPACENET, WIPO/PATENTSCOPE, National Institute of Industrial Property (INPI), Google Patents). The main materials utilized for the impression, as well as the physical characteristics of the device are introduced at first. Crucial aspects to facilitate proper visualization of the anatomical structures during endotracheal intubation as the optimal angulation of the blade, the mechanical resistance of the device, traction force on the jaw, intubation time, and the experimental methods employed to validate its performance were reviewed in terms of their recent advances.